2022
DOI: 10.7150/ijbs.68179
|View full text |Cite
|
Sign up to set email alerts
|

Flap endonuclease 1 Facilitated Hepatocellular Carcinoma Progression by Enhancing USP7/MDM2-mediated P53 Inactivation

Abstract: Overexpression of Flap endonuclease 1 (FEN1) has been previously implicated in hepatocellular carcinoma (HCC), while its expression features and mechanisms remain unclear. In the current study, differential expression genes (DEGs) were screened in HCC tissues and normal liver tissues in 4 Gene Expression Omnibus (GEO) datasets. FEN1, one of the hub co-overexpressed genes, was further determined overexpressed in HCC tissues in TCGA, local HCC cohorts, and hepatocarcinogenesis model. In addition, high expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Furthermore, Saiyan et al. ( 15 ) suggested that Flap endonuclease 1 Facilitated hepatocellular carcinoma progression by enhancing USP7/MDM2-mediated P53 inactivation. However, previous bioinformatics studies were relatively simple: no multi-omics integration analysis or assessment of tumor mutation burden (TMB) was used, or focusing on exploration of the single gene, or without experimental validation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Saiyan et al. ( 15 ) suggested that Flap endonuclease 1 Facilitated hepatocellular carcinoma progression by enhancing USP7/MDM2-mediated P53 inactivation. However, previous bioinformatics studies were relatively simple: no multi-omics integration analysis or assessment of tumor mutation burden (TMB) was used, or focusing on exploration of the single gene, or without experimental validation.…”
Section: Introductionmentioning
confidence: 99%
“…FEN1 has been found to have abnormal expression or mutation in a variety of solid tumors, which has promoted the proliferation and migration of tumor cells [ 50 ]. FEN1 has also been found to be closely related to tumor chemotherapy resistance, and is considered to be a marker of metastasis and poor prognosis of various malignant tumors [ 61 ]. Therefore, FEN1 is considered to be an effective target for the treatment of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…These breaks activated the G2/M checkpoint protein Chk1 and induced near-tetraploid aneuploidy, promoting the development of aneuploid cancers. Overexpression of FEN can promote the proliferation, cell cycle, migration or invasion, drug resistance, xenograft growth and epithelial mesenchymal transition (EMT) of hepatoma cells [ 61 ]. In addition, the abnormally high expression of IGF2BP2, a key gene in the m6A signaling pathway, was found in HCC cells.…”
Section: The Role Of Fen1 In Diseasesmentioning
confidence: 99%
“…Biomarkers commonly used as part of routine clinical practice can complement clinical examination and contribute to the management of various diseases. The advance of the new sequencing approach and access to some huge genetic and epigenetic databases including TCGA and GEO, are providing potential biomarkers options and the focus is shifting to a combination of several or more biomarkers, rather than a single marker that researchers have concentrated on in the past ( Conway and Wong, 2020 ; Vincent et al, 2020 ; Bian et al, 2022 ). In this study, we conducted an integrative analysis of gene expression and DNA methylation data, and identified the DMGs and DEGs between PD patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%